CONSUMER WARRANTY AS A GENRE - DELEKTA, Ilona (Comparative Legilinguistics, 2013)
The purpose of this paper is to present genre specificity of the consumer warranty and various factors determining its structure and language as well as consumer regulations. Warranty is a type of document that is commonly used and widely known. However, a possibility of different interpretations of warranty content can lead to its incomprehensibility and/or misinterpretation and have s pecific legal consequences. The author analysed English version of 110 warranty documents for consumer goods. The collected research material indicates a structural and syntactic diversity ofwarranty documents. It also illustrates how content and the language of the document might facilitate or hinder its correct interpretation.